2020
DOI: 10.3390/cells9051174
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Kinase and Progression Rate in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease with no recognized clinical prognostic factor. Creatinine kinase (CK) increase in these patients is already described with conflicting results on prognosis and survival. In 126 ALS patients who were fast or slow disease progressors, CK levels were assayed for 16 months every 4 months in an observational case-control cohort study with prospective data collection conducted in Italy. CK was also measured at baseline in 88 CIDP patients with second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…As reported in Fig. 5a, the CPK levels decrease in both fast and slow progressing patients in line with previous evidence 21,22 , and the linear regression analysis highlighted a significant difference in the slope of the CPK linear curve. In particular, the slope or rate decline of the slow progressing patients resulted significantly smaller compared with the fast progressing ones (p ≤ 0.001).…”
Section: Mirnas Expression Levels Are Differentially Modulated In Slosupporting
confidence: 90%
“…As reported in Fig. 5a, the CPK levels decrease in both fast and slow progressing patients in line with previous evidence 21,22 , and the linear regression analysis highlighted a significant difference in the slope of the CPK linear curve. In particular, the slope or rate decline of the slow progressing patients resulted significantly smaller compared with the fast progressing ones (p ≤ 0.001).…”
Section: Mirnas Expression Levels Are Differentially Modulated In Slosupporting
confidence: 90%
“…Since CK is an enzyme involved in the muscle's energy metabolism (19), some researchers also assumed that upregulation improves muscle energy and function. This is supported by the finding that patients with higher CK levels tend to show slower progression (20,33) and that CK declines faster in rapidly progressive disease (50). We found an association between rate of decay and CK levels in the linear univariate model, but the result was not reproducible in the multivariate model including basic variables.…”
Section: Creatine Kinase (Ck)mentioning
confidence: 80%
“…There is also evidence of elevated serum CK levels in the early stage of sALS 36 . Changes in the blood CK activities in patients with ALS were recently presented in a new perspective, with higher CK levels reported for an ALS model with a slowly progressing disease than in an ALS model with a fast-progressing disease 37 . The study suggested that the slow-progressing mice progress slower because they have greater muscle mass and may counter disease mechanisms for more extended periods than the fast-progressing mice 37 .…”
Section: Discussionmentioning
confidence: 99%